The surfactant dipalmitoylphophatidylcholine modifies acute responses in alveolar carcinoma cells in response to low‐dose silver nanoparticle exposure. Issue 10 (16th April 2015) - Murphy, A.; Sheehy, K.; Casey, A.; Chambers, G.
Abstract: Nanotechnology is a rapidly growing field with silver nanoparticles (AgNP) in particular utilized in a wide variety of consumer products. This has presented a number of concerns relating to exposure and the associated toxicity to humans and the environment. As inhalation is the most common exposure route, this study investigates the potential toxicity of AgNP to A549 alveolar epithelial carcinoma cells and the influence of a major component of lung surfactant dipalmitoylphosphatidylcholine (DPPC) on toxicity. It was illustrated that exposure to AgNP generated low levels of oxidative stress and a reduction in cell viability. While DPPC produced no significant effect on viability studies its presence resulted in increased reactive oxygen species formation. DPPC also significantly modified the inflammatory response generated by AgNP exposure. These findings suggest a possible interaction between AgNP and DPPC causing particles to become more reactive, thus increasing oxidative insult and inflammatory response within A549 cells. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Inhalation presents as the most common route of silver nanoparticle (AgNP) exposure. As such, its interaction with pulmonary surfactant may influence the biological response induced. Toxicological testing was performed on the A549 cell line and it demonstrated toxicity induced by AgNP exposure. Significant changes in acute responses including reactive oxygen species generation and inflammatory marker release was noted. It is postulated that the presence of dipalmitoylphosphatidylcholine interacts with AgNP producing a more reactive particle resulting in modification of acute responses at low dose exposures